The state, antisemitism, and collaboration in the Holocaust : the borderlands of Romania and the Soviet Union - Dumitru, Diana (Cambridge University Press, 2016)
1. Experiencing the Russian empire -- 2. Bessarabia within the Romanian state: antisemitism reframed -- 3. Committed to change: fighting antisemitism and integrating Jews in Soviet Transnistria -- 4. Under assault: civilians' behavior toward Jews during the Holocaust in Bessarabia -- 5. Jews and their neighbors in occupied Transnistria -- 6. Substantiating and explaining the differences